'Over‐communication' keeps students in the loop and increases enrollment despite COVID‐19 uncertainty. Issue 10 (23rd December 2020) - Bannister, Mary
Abstract : "We've worked to speak to the student as much as we can, " said Rosaria Guastella, Vice President for Enrollment Management at the University of Holy Cross. Although campus tours and orientation happened virtually this year, UHC officials worked to get to know the students they were admitting and to convey the spirit of the university. Using both in‐person and virtual events, social media, texting, and enthusiastic student ambassadors, UHC officials maintained enrollment numbers for the class of 2024. With students engaging from both near and far, many virtually, "we're meeting them where they are — literally in this case, " Guastella said.